Penerapan Konsep Total Productive Maintenance pada Mesin Automatic Bottle Filling - Yon Pradana; Rosleini Ria Putri Zendrato; Bagus Ismail Adhi Wicaksana (Program Studi Teknik Industri Universitas Setia Budi, 2019)
Guwatirta Sejahtera is one of the companies engaged in the bottled drinking water industry. Problems that occur at PT. Guwatirta Sejahtera is the absence of routine maintenance on the machine so that damage, especially on automatic bottle filling machines, often occurs. This study applies a total productive maintenance method to determine the level of damage and identify the source of the problem as a basis for making recommendations for improvement in reducing the level of damage that often occurs in automatic bottle filling machines. The stage of the study begins by determining the engine efficiency and six big losses using the Overall Equipment Effectiveness parameter (OEE). Then proceed with identifying the source of the problem using the Failure Mode and Effect Analysis (FMEA) method. Recommendations for improvement include making: a daily inspection checklist, small working groups, Standard Operating Procedures for operating the machine and routine maintenance schedules. Based on the estimated calculation if the recommendation for improvement is applied, the value of the original engine efficiency of 84.26% increased to 98.97% and the initial maintenance costs of Rp.81,232,369.48 decreased to Rp.75,355,764.39 per year